2001
DOI: 10.1080/135502801753248150
|View full text |Cite
|
Sign up to set email alerts
|

Association of human herpesvirus 6 and human herpesvirus 7 with demyelinating diseases of the nervous system

Abstract: Peripheral blood mononuclear cells and plasma of 113 patients with neurological disorders and 150 blood donors were analyzed for HHV-6 and HHV-7 sequences by PCR. The prevalence of HHV-6 was significantly higher in patients with multiple sclerosis (P < 0.01) than in cases of nondemyelinating diseases of the central and demyelinating diseases of the peripheral nervous systems and blood donors. HHV-6 viremia was found only in patients with multiple sclerosis, predominantly in the active phase of the disease. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 35 publications
0
10
0
1
Order By: Relevance
“…The central nervous system (CNS) seems to be one of the reservoirs for persistent HHV-7 infection, since specific genomic sequences can be detected by PCR ( 61 , 62 ). Nonetheless, HHV-7 reactivation measured by specific qPCR of blood samples is also associated with demyelinating diseases of the peripheral nervous system (PNS) ( 6 ). Most interestingly, we observed MneHV7-specific staining of nerve ganglia innervating the salivary glands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The central nervous system (CNS) seems to be one of the reservoirs for persistent HHV-7 infection, since specific genomic sequences can be detected by PCR ( 61 , 62 ). Nonetheless, HHV-7 reactivation measured by specific qPCR of blood samples is also associated with demyelinating diseases of the peripheral nervous system (PNS) ( 6 ). Most interestingly, we observed MneHV7-specific staining of nerve ganglia innervating the salivary glands.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the cells stained in the nerve ganglia show a structure reminiscent of that of Schwann cells. Since HHV-7 reactivation is associated with demyelinating processes in humans ( 6 ), it is tempting to speculate that Schwann cells are susceptible to MneHV7 infection. MneHV7 lytic infection of Schwann cells could be associated with a decrease in myelin expression, resulting in demyelinating neuropathies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the last decades, it has been hypothesized that an environmental factor may be involved in the disease, triggering autoimmune attack against nerve cells in genetically susceptible individuals [5]. Recently, several articles [5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25]have reported that human herpesvirus-6 (HHV-6), a highly prevalent virus in human population, could be this agent; two variants of HHV-6 (HHV-6A and HHV-6B) have been identified, but only the HHV-6A variant, a neurotropic virus, has been suggested to have a pathogenic role in MS, and specifically, in exacerbations [8, 17, 22]. …”
Section: Introductionmentioning
confidence: 99%
“…It is not clear which factors are responsible for the different courses [9]. No virus has been definitively implicated as a causative factor of MS, but certain HHVs have been linked with the development of MS [10, 11]. Since the first papers linking HHV-6 to MS appeared in 1993 [12] many others have presented contradictory results on its possible role in the disease.…”
Section: Introductionmentioning
confidence: 99%